Spatial analysis on human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS) cases in the Philippines - Tandang, Nancy A.; Aguila, Lysette C. (2016)
The human immunodefiency virus (HIV) causing HIV infection and acquired immunodeficiency syndrome (AIDS) has been a growing public health concern in many developed and developing countries. Due to the rapid increase in the number of HIV infection and AIDS cases in the Philippines, this study investigated HIV infection and AIDS prevalence in the country, its spread across neighboring provinces, and its possible explanatory factors. Statistical spatial analysis, a classic statistical analysis was performed to incorporate the effects of spatial or geographical characteristics. Using a neighborhood criteria (Queen's contiguity, distance-band with cut-off distance set to 250 km, ad k-nearest neighbors with k set to 5), the results showed that provinces of Batangas, Bulacan, Cavite, Laguna, Rizal, and Metropolitan Manila were considered to be in the high-high cluster, indicating these areas to have a higher HIV infection and AIDS or cases than the national estimate. Using spatial lag modeling, increasing population density and number of HIV infection and AIDS cases. On the other hand, additional barangay health stations and barangay health workers were noted to be contributory factors in the reduction of HIV infection and AIDS cases in the country.
Keywords: AIDS (Disease)